Potential of Nanotechnology-based Formulations in Combating Pulmonary Infectious Diseases: A Current Scenario - Patel, Manisha; Mazumder, Rupa; Mishra, Rakhi; Kant Kaushik, Kamal (Current Pharmaceutical Design, 2022)
Background: Pulmonary microbial infection is mainly caused by microbes like atypical bacteria, viruses, and fungi, on both the upper and lower respiratory tracts. One of the demands of the present is the use of nanotechnology-based treatments to fight various lung infections. Aim: The main aim of the study is to explore all pulmonary infectious diseases and to compare the advanced and novel treatment approaches with the conventional methods which are available to treat infections. Methods: This work sheds light on pulmonary infectious diseases with their conventional and present treatment approaches along with a focus on the advantageous roles of nano-based formulations. In the literature, it has been reported that the respiratory system is the key target of various infectious diseases which gives rise to various challenges in the treatment of pulmonary infections. Results: The present review article describes the global situation of pulmonary infections and the different strategies which are available for their management, along with their limitations. The article also highlights the advantages and different examples of nanoformulations currently combating the limitations of conventional therapies. Conclusion: The content of the present article further reflects on the summary of recently published research and review works on pulmonary infections, conventional methods of treatment with their limitations, and the role of nano-based approaches to combat the existing infectious diseases which will jointly help the researchers to produce effective drug formulations with desired pharmacological activities.
Keywords: lung infections